Metal-insulator transitions in the two dimensional ionic Hubbard model within coherent potential approximation - NGUYEN, Thi Hai Yen; Hoang Anh, Tuan (Communications in Physics, 2026)
We employ the coherent potential approximation to investigate the phase diagram of the ionic Hubbard model on the square lattice. The results show the existence of two insulating phases: a band insulator in the regime of large ionic potential Δ and small Coulomb interaction U, and a Mott insulator in the regime of large U. Between these two insulating phases, a metallic phase emerges as an intermediate state. The obtained phase diagram is compared to those on the Bethe lattice.